The university state and the generation of fear and uncertainty: limited academic output in undergraduate programmes at a public university - Ramos Morales, Leonidas Lucas (2025)
In Peru, the number of undergraduate programs, students, and faculty in political science has increased in recent years; however, this growth has not been accompanied by a corresponding increase in the academic output of graduates, a deficiency particularly evident in public universities. The objective of this research is to analyze the academic output in political science of students and graduates of the National University of San Marcos over the last twenty years. The study employs a mixed-methods approach, with an emphasis on the qualitative dimension, applying tools typical of state ethnography. The results show that, despite having one of the largest student populations, outstanding physical infrastructure, and significant resources, the program registers low levels of theses and professional competency projects, in addition to a considerably long average completion time. Regarding the topics addressed, those related to public administration predominate, although they have not achieved significant academic impact. This critical situation is explained by two main factors: on the one hand, the process of preparing the documents takes place in an institutional environment —marked by administrative procedures, teachers, advisors and juries— that produces fear and uncertainty, which tends to paralyze students and graduates; on the other hand, many prioritize rapid job placement over the production of knowledge, in a frightening critical context marked by vulnerable family backgrounds and a state labor market characterized by deinstitutionalization.